Overexpression of NEUROG2 and NEUROG1 in human embryonic stem cells produces a network of excitatory and inhibitory neurons. Issue 4 (30th January 2019) - Lu, Congyi; Shi, Xi; Allen, Andrew; Baez‐Nieto, David; Nikish, Alexandria; Sanjana, Neville E.; Pan, Jen Q.
ABSTRACT: Overexpression of mouse neurogenin (Neurog)2 alone or in combination with mouse Neurog2/1 in human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs) can rapidly produce high‐yield excitatory neurons. Here, we report a detailed characterization of human neuronal networks induced by the expression of human NEUROG2 together with human NEUROG2/1 in hESCs using molecular, cellular, and electrophysiological measurements over 60 d after induction. Both excitatory synaptic transmission and network firing activity increased over time. Strikingly, inhibitory synaptic transmission and GABAergic cells were identified from NEUROG2/1 induced neurons (iNs). To illustrate the application of such iNs, we demonstrated that the heterozygous knock out of SCN2A, whose loss‐of‐function mutation is strongly implicated in autism risk, led to a dramatic reduction in network activity in the NEUROG2/1 iNs. Our findings not only extend our understanding of the NEUROG2/1 ‐induced human neuronal network but also substantiate NEUROG2/1 iNs as an in vitro system for modeling neuronal and functional deficits on a human genetic background.—Lu, C., Shi, X., Allen, A., Baez‐Nieto, D., Nikish, A., Sanjana, N. E., Pan, J. Q. Overexpression of NEUROG2 and NEUROG1 in human embryonic stem cells produces a network of excitatory and inhibitory neurons. FASEB J. 33, 5287–5299 (2019). www.fasebj.org